MEWUJUDKAN GURU YANG BERKARAKTER CERDAS DAN KUAT MELALUI PENERAPAN PAIKEM GEMBROT MODEL WEBBED DALAM MATERI BUDAYA POLITIK - ., Muhari (PKn Progresif, 2012)
Teachers realize the intelligent and strong character can be done through the application of fat Paikem webbed models in the matter of political culture. Teachers can not leave the students during the learning takes place but must make the observation of students' learning activities and provide continuous reflection. Teachers must have the intelligence to provide a reflection that has a strong influence for students.